From Engineering and Technological Process to Post-Cultural Technology - Vadim Rozin (International Society of Philosophy and Cosmology, 2021)
The article discusses the dilemma of "technology or technologies," as well as the nature of the Internet as one of the types of technology of the future ("post-culture"). Reflections lead the author to the thesis about not one, but many technologies. The ideas of engineering and technological process and two different understandings of technology ? as an activity of the creation of technical products and formation of technical environment essentially defining human life are differentiated. According to the author, the technological process's formation was promoted by the activity inflection point and the inflection point, which was later associated with management. The article ends with a discussion of the Internet as a new type of technology.